2018
DOI: 10.3390/app8060893
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Assessment of the Convective Heat Transfer in Rotating Detonation Combustors Using a Reduced-Order Model

Abstract: The pressure gain across a rotating detonation combustor offers an efficiency rise and potential architecture simplification of compact gas turbine engines. However, the combustor walls of the rotating detonation combustor are periodically swept by both detonation and oblique shock waves at several kilohertz, disrupting the boundary layer, resulting in a rather complex convective heat transfer between the fluid and the solid walls. A computationally fast procedure is presented to calculate this extraordinary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(5 citation statements)
references
References 33 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…Analysing the strengths and weaknesses of each of the approaches mentioned earlier, a research framework was developed to obtain a reduced-order numerical (ROM) model to achieve the most effective solution for the problem concerned. A ROM provides similar accuracy as 3D CFD models in solving complex scenarios but requires significantly less computational resources and time [40]. This study aimed to develop a (1 + 1)D reduced-order numerical model that could (1) be validated by the results of an experimental investigation, (2) provide the same accuracy as a 3D finite element (FE) model for different operating and design parameters and (3) be applied to establish an energy-efficient large-scale design for injecting flue gas into mine tailings.…”
Section: Introductionmentioning
confidence: 99%
“…Analysing the strengths and weaknesses of each of the approaches mentioned earlier, a research framework was developed to obtain a reduced-order numerical (ROM) model to achieve the most effective solution for the problem concerned. A ROM provides similar accuracy as 3D CFD models in solving complex scenarios but requires significantly less computational resources and time [40]. This study aimed to develop a (1 + 1)D reduced-order numerical model that could (1) be validated by the results of an experimental investigation, (2) provide the same accuracy as a 3D finite element (FE) model for different operating and design parameters and (3) be applied to establish an energy-efficient large-scale design for injecting flue gas into mine tailings.…”
Section: Introductionmentioning
confidence: 99%
“…This requires kinematic viscosities of the H 2 gas calculated from dynamic viscosities and gas densities at each elevation. The dynamic viscosities of H 2 in this calculation are obtained from the temperature-dependent Sutherland constants for hydrogen gas from Braun et al (2018) and ideal gas densities corresponding to the atmospheric H 2 pressures. The terminal velocities depend on the diameter of the pebbles.…”
Section: Application To Pebble Accretionmentioning
confidence: 99%
“…Through 3-D numerical simulation results, Dubrovskii et al [42] reported that the maximum heat flux of the inner wall near the bottom of the RDC was about 1.7 MW/m 2 , while the maximum heat flux of the outer wall was about 0.95 MW/m 2 at a distance of 150-200 mm from the bottom of the RDC. In order to quantitatively predict the convective heat flux in an RDE, Braun et al [43] established a reducedorder model using unsteady Reynolds-averaged Navier-Stokes CFD with premixed hydrogen and air as the propellant. The peak time-averaged heat flux was predicted to be about 6 MW/m 2 at the triple point, followed by a downstream decrease in the oblique shock.…”
Section: Introductionmentioning
confidence: 99%